Car crisis and renewal: how Mercedes succeeded with the A-Class. Issue 1 (15th January 2018) - Tournois, Laurent; Chanaron, Jean-Jacques
Abstract : Purpose: In mature industries, downward vertical (line) extension has become an increasingly popular strategy, particularly for automobile manufacturers aiming at expanding their consumer bases and/or avoiding competition in higher market segment. This paper aims to examine how Mercedes-Benz (MB) practiced a downward vertical line extension within the same product category. When commercialized as a product line innovation, the MB A-Class was the first and most symbolic move made by a premium brand in the automobile industry. Design/methodology/approach: This paper investigates the microfoundations of a vertical downward extension strategy. To do so, the authors adopt a narrative style to analyze the story of the MB A-Class from its inception to its commercialization. Secondary data sources, such as company websites, annual reports, internal documents, books, public relations and press releases, were used. Qualitative as well as quantitative performance outcomes were assessed using market and product sales in Western Europe (1997-2016) and the results of an MB brand image survey conducted in 1998 following the accident faced by the A-Class. Findings: The case illustrates that contrary to initial assumptions, lower-quality extensions may be relevant for prestige brands under certain conditions and identifies four strategy components that may drive a successful downward stretch: combine organizational, product, process and marketing innovation with the support of dynamic capabilities; manage paradoxes/contradictions in terms of product development; target the high-end of a lower consumer segment; and adopt a "brand humility talk scheme". Research limitations/implications: Existing studies primarily focus on consumers' evaluations of vertical step-down extensions. Rare are the articles that adopt the company's perspective. Moreover, additional research is needed to assess the short- and long-term impacts of vertical downward extension on performance outcomes. Practical implications: The case of the MB A-Class encourages top executives to consider the trade-offs inherent to a down-market strategic move: keeping the (premium) brand's standards high within a reduced cost/price envelope while learning the codes of the new/bottom of the market. In addition, the A-Class may serve as a fundamental school case for marketing managers and creative advertising agencies on what should and should not be done, whether at the product or at the advertising level. Originality/value: This paper demonstrates that a premium brand that practiced a vertical downward line extension can expand its sales in a mass market, by targeting a small but growing segment with a high willingness to pay for more expensive products. This adds to the contention that it is not the downscale extension product price per se that negatively affects the parent brand but rather where it stands in the hierarchy of the market segment considered and the ability of the premium brand to integrate the downscale extension to its own history (i.e. combining its original values with tangible product benefits while backing the cause of the new market). Finally, the story of the A-Class strongly suggests that any company needs to upgrade its capabilities as part of the learning process of a new market to convert a business opportunity into a market success.